2003
DOI: 10.1152/ajpcell.00092.2003
|View full text |Cite
|
Sign up to set email alerts
|

Localization and interaction of NHERF isoforms in the renal proximal tubule of the mouse

Abstract: In expression systems and in yeast, Na/H exchanger regulatory factor (NHERF)-1 and NHERF-2 have been demonstrated to interact with the renal brush border membrane proteins NHE3 and Npt2. In renal tissue of mice, however, NHERF-1 is required for cAMP regulation of NHE3 and for the apical targeting of Npt2 despite the presence of NHERF-2, suggesting another order of specificity. The present studies examine the subcellular location of NHERF-1 and NHERF-2 and their interactions with target proteins including NHE3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
102
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 32 publications
10
102
0
Order By: Relevance
“…However, they retain megalin/ ClC-5-and NHE3-dependent albumin uptake pathways (36,50), and NHE3 is reported to traffic from the microvilli to the intravillar regions (34). Importantly, the distribution of NHERF1 in the microvilli domain and NHERF2 in regions between the microvilli that we report corresponds to their distributions in the mouse and human proximal tubules (29,31), thus OK cells are a suitable model for the investigation of the molecular basis of receptor-mediated albumin uptake (see Ref. 2).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, they retain megalin/ ClC-5-and NHE3-dependent albumin uptake pathways (36,50), and NHE3 is reported to traffic from the microvilli to the intravillar regions (34). Importantly, the distribution of NHERF1 in the microvilli domain and NHERF2 in regions between the microvilli that we report corresponds to their distributions in the mouse and human proximal tubules (29,31), thus OK cells are a suitable model for the investigation of the molecular basis of receptor-mediated albumin uptake (see Ref. 2).…”
Section: Discussionsupporting
confidence: 62%
“…NHERF proteins clearly have the capacity to nucleate the formation of functional complexes at the plasma membrane (30,32) and restrict the mobility of plasma membrane proteins, such as NHE3 (33,34). Thus the organized subcellular distribution of NHERF1/2 is speculated to play a role in the specific interactions that mediate the physiological regulation of transporter function (31). The current study was therefore undertaken to investigate the potential involvement of NHERF1/2 in albumin uptake and whether this involved interactions with ClC-5, a key component of the albumin endocytic complex.…”
mentioning
confidence: 99%
“…Importantly, although NHERF-1 and NHERF-2 were originally described in the kidney, Northern blot analysis shows an overlapping and wide-spread distribution pattern for NHERF-1 and NHERF-2 mRNAs in human tissues, including brain, heart, colon, small intestine, liver, prostate, spleen, and placenta (Weinman et al 1995;Yun et al 1997). Immunohistochemical studies have demonstrated NHERF-1 and NHERF-2 in the human (Weinman et al 2002) and mouse (Wade et al 2003) kidney, NHERF-1 in the mouse retina (Nawrot et al 2004) and Schwann cell processes (Gatto et al 2003), and NHERF-2 in endothelia and pericytes from rat descending vasa recta (Lee-Kwon et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, its close relative NHERF-2 (also called E3KARP) was cloned and characterized (Yun et al 1997). NHERF-1 and NHERF-2 consist of 358 and 337 amino acids, respectively, sharing 54% homology and possess two PDZ domains and a C-terminal ezrin-radixin-moesinmerlin (ERM)-binding domain that can interact with the actin cytoskeleton (Fanning and Anderson 1999;Shenolikar and Weinman 2001;Wade et al 2003;Yun 2003;Shenolikar et al 2004). NHERF-1 and NHERF-2 bind PDZ motifs in the C-termini of target proteins to assemble signaling/transport complexes at the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is well known that NaPi-2a is integrated in a series of macromolecular complexes whose architecture is based on PDZ (PSD-95, discs-large, and ZO-1) protein interactions (12)(13)(14)(15)(16)(17)(18)(19). NaPi-2a participates in this complex by means of a class I PDZ-binding site located at its C terminus, comprising its last three amino acids (TRL).…”
mentioning
confidence: 99%